"BINGE DRINKING": CLINICAL AND SOCIAL ASPECTS IN PEDIATRIC EMERGENCIES - CASE PRESENTATION - V.E. Roșu; Elena Țarcă; Oana Lăcrămioara Bădărău; Solange Tamara Roșu (Romanian Society of Oral Rehabilitation, 2019)
Specialized studies and practical experience indicate that the primary cause for ethyl alcohol intoxication in teenagers is the binge-drinking type of alcohol consumption. Binge-drinking entails the episodic paroxysmal ingestion of a large quantity of alcohol over a short period of time, with both short and long term clinical and social implications. The article presents the features and evolution of a 17-year-old male patient after binge-drinking alcohol. Such cases are medical, psychiatric and forensic medicine emergencies in a pediatric emergency department.